Electrostatic Mechanophores in Tuneable Light‐Emitting Piezopolymer Nanowires. Issue 29 (1st June 2017) - Persano, Luana; Camposeo, Andrea; Terentjevs, Aleksandr V.; Della Sala, Fabio; Fabiano, Eduardo; Montinaro, Martina; Pisignano, Dario
Abstract : Electromechanical coupling through piezoelectric polymer chains allows the emission of organic molecules in active nanowires to be tuned. This effect is evidenced by highly bendable arrays of counter‐ion dye‐doped nanowires made of a poly(vinylidenefluoride) copolymer. A reversible redshift of the dye emission is found upon the application of dynamic stress during highly accurate bending experiments. By density functional theory calculations it is found that these photophysical properties are associated with mechanical stresses applied to electrostatically interacting molecular systems, namely to counterion‐mediated states that involve light‐emitting molecules as well as charged regions of piezoelectric polymer chains. These systems are an electrostatic class of supramolecular functional stress‐sensitive units, which might impart new functionalities in hybrid molecular nanosystems and anisotropic nanostructures for sensing devices and soft robotics. Abstract : Electromechanical coupling through piezoelectric polymers tunes the emission of organic molecules in active nanowires. Highly bendable arrays of counter‐ion dye‐doped wires made of a poly(vinylidenefluoride) copolymer are realized, which show a reversible shift of the emission upon applying dynamic stress during bending. Electrostatic mechanophores may provide anisotropic molecular systems with an optical sensing capability for monitoring local stress and damage in transparent materials, optoelectronics, and soft robotics.